The genera Carpias Richardson, Ianiropsis Sars and Janaira Moreira & Pires (Isopoda: Asellota: Janiridae) from Australia, with description of three new species - Doti, Brenda Lía (2010)
Three new species of janirid isopods are described: Carpias montaguensis sp. nov., Ianiropsis alanmillari sp. nov. and Janaira platyoura sp. nov.; all three were collected in shallow waters of southern New South Wales, Australia. Our report represents new records for these genera in Australian waters. Janaira platyoura sp. nov. is the second species added to this genus, so a revision of generic diagnosis was required. The diagnostic features of Carpias and Ianiropsis are also discussed and a new combination for the species Ianiropsis varians Winkler & Brandt, 1993 is proposed. Keys to the species of Carpias and Ianiropsis are presented.